2019
DOI: 10.1186/s12935-019-0793-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic value of ZEB1 protein expression in breast cancer patients with neoadjuvant chemotherapy

Abstract: Background Zinc finger E-box binding homeobox 1 (ZEB1) is a molecule involved in the progression of epithelial-to-mesenchymal transition (EMT) in various kinds of cancers. Here, we aimed to determine whether the expression of the ZEB1 protein is related to the response of patients to neoadjuvant therapy as well as their survival outcome. Methods Immunohistochemistry (IHC) was performed on paraffin-embedded tumor samples from core needle biopsy before neoadjuvant therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…A transcription regulator ZEB1 targets E-cadherin repression which is a prerequisite for EMT state. So, it is noteworthy that the EMT status linked to ZEB1 expression does not only indicate the mechanistic steps of disease pathogenesis but also it could be a potential therapeutic target [90,91]. Moreover, ZEB1 protein expression has some predictive outcome during neoadjuvant therapy in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A transcription regulator ZEB1 targets E-cadherin repression which is a prerequisite for EMT state. So, it is noteworthy that the EMT status linked to ZEB1 expression does not only indicate the mechanistic steps of disease pathogenesis but also it could be a potential therapeutic target [90,91]. Moreover, ZEB1 protein expression has some predictive outcome during neoadjuvant therapy in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Proper staging is critical for determining the appropriate clinical treatment course and surgical planning. Neoadjuvant therapies, where patients receive systemic therapy before surgical removal of the tumor, can downstage tumors allowing breast-conserving surgery, rather than mastectomy [91,95]. The effectiveness of standard and/or potential new therapies can be tested in the neoadjuvant pre-surgical setting [91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vimentin has been considered to be an EMT marker that is ubiquitously expressed in normal mesenchymal cells and exerts its effect to maintain cellular integrity [35]. ZEB1 is zinc finger E-box binding homeobox 1 that involved in the progression of EMT in various kinds of cancers [36]. Furthermore, the EMT process was described by lacking cell-cell adhesion, which has an association of migratory and invasive features [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that ZEB1 (Zinc Finger E-box Binding Homeobox 1) has an active role in the induction of EMT in diverse epithelial malignancies, such as colon, prostate, pancreas, lung and breast cancer (1015). Notably, the expression of ZEB1 in these tumors correlates with the loss of E-cadherin and is associated with advanced or metastatic disease, by triggering combined activation of cell motility and stemness properties (10, 16–18).…”
Section: Introductionmentioning
confidence: 99%